Discovery of (R)-2-amino-3-triazolpropanoic acid derivatives as NMDA receptor glycine site agonists with GluN2 subunit-specific activity - Zhao, Fabao; Mazis, Georgios; Yi, Feng; Lotti, James S.; Layeux, Michael S.; Schultz, Eric P.; Bunch, Lennart; Hansen, Kasper B.; Clausen, Rasmus P. (Frontiers in Chemistry, 2022)
N-Methyl-D-aspartate (NMDA) receptors play critical roles in central nervous system function and are involved in variety of brain disorders. We previously developed a series of (R)-3-(5-furanyl)carboxamido-2-aminopropanoic acid glycine site agonists with pronounced variation in activity among NMDA receptor GluN1/2A-D subtypes. Here, a series of (R)-2-amino-3-triazolpropanoic acid analogues with a novel chemical scaffold is designed and their pharmacological properties are evaluated at NMDA receptor subtypes. We found that the triazole could function as a bioisostere for amide to produce glycine site agonists with variation in activity among NMDA receptor subtypes. Compounds 13g and 13i are full and partial agonists, respectively, at GluN1/2C and GluN1/2D with 3- to 7-fold preference in agonist potency for GluN1/2C-D over GluN1/2A-B subtypes. The agonist binding mode of these triazole analogues and the mechanisms by which the triazole ring can serve as a bioisostere for amide were further explored using molecular dynamics simulations. Thus, the novel (R)-2-amino-3-triazolpropanoic acid derivatives reveal insights to agonist binding at the GluN1 subunit of NMDA receptors and provide new opportunities for the design of glycine site agonists.